A new species of planthopper in the genus Patara (Hemiptera: Derbidae) on coconut palm (Cocos nucifera) from the island of Barbuda - Bahder, Brian W.; Gore-Francis, Janil; Bartlett, Charles R. (Zootaxa, 2021)
The island of Barbuda was recently surveyed for the presence of Haplaxius crudus to establish the risk of Lethal Yellowing to palms on the island. After extensive collecting, H. crudus was not found on the island. A new species of Patara Westwood was found on coconut palms on the southwest portion of Barbuda. Herein, we describe the new species as Patara cooki sp. n. and provide DNA sequence data for cytochrome c oxidase subunit I (COI) and 18S genes for it and Patara guttata Westwood. Patara cooki differed from Patara guttata sp. n. by 1.8% for 18S and 7.8% for COI, similar to intrageneric differences reported for other taxa. A phylogenetic analysis of available Otiocerinae near Patara using found Patara cooki sp. n. nested among other Patara species. We also offer commentary regarding the interpretation of forewing venation in Patara.